Megaincendio de febrero de 2024 en la conurbación de la provincia de Valparaíso y zonas de interfaz urbano-forestal, Chile - Castañeda-Meneses, Patricia Lorena (2025)
On February 2 and 3, 2024, the conurbation of the Province of Valparaíso, Chile, was affected by a catastrophic megafire. In this context, the article presents the results of a qualitative study with an exploratory-descriptive approach, aimed at analyzing the event from the perspective of the contribution of wildland-urban interface zones to the occurrence of the disaster. The findings show that the wildland-urban interface zones of the Valparaíso conurbation constituted a powerful fuel load that increased the territory’s vulnerability to the megafire. This vulnerability was exacerbated by high temperatures, low humidity, and strong winds, resulting in a high destructive potential that reached an unprecedented level of devastation. There is a high risk that such an event will recur in the territory, given the structural geographic conditions that favor the presence of wildland-urban interface zones, compounded by a decade-long megadrought, the existence of fast-growing forest plantations on urban margins, and human impact. It is concluded that the occurrence of the megafire is linked at a macro level to the process of climate change and its consequences—megadrought and heat waves—factors that, in this case, contributed to the development of a catastrophic event.